Mudharabah, musyarakah, financing risk, and performance of Islamic banks: Empirical evidence from Indonesia - Annizar, Radhita Asfarina; Junarsin, Eddy (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study examines the effects and thresholds of mudharabah and musyarakah on the financing risk and performance of Indonesian Islamic banks. Methodology – Using panel data and quadratic regression analysis, we explore the nonlinear relationships among mudharabah, musyarakah, financing risk, and performance of Islamic banks in Indonesia using a sample of 14 Indonesian Islamic banks during the period to 2008-2020.Findings – We find that mudharabah is negatively related to financing risk and positively (in the initial stage) linked to Islamic bank performance. Mudharabah will reduce financing risk if the proportion of mudharabah to total loans is in the range of 5.5-12.6%. A proportion of mudharabah below 5.5% or above 12.6% worsens non-performing financing (NFP), loan loss provision (LLP), and Z-score. In contrast, musyarakah is found to be positively (although marginally) related to financing risk and negatively and weakly associated with the performance of Indonesian Islamic banks. Implications – Our findings have consequential implications for both practitioners and policymakers. Understanding the dual effects of mudharabah and musyarakah can help to implement strategies that optimize investment portfolios, enhance profitability, and minimize risk. For policymakers, these results highlight the need for regulatory frameworks that encourage optimum thresholds of mudharabah financing to mitigate risk while spurring performance. Originality – This study contributes to the literature by identifying a turning point in mudharabah financing that minimizes financing risk, a realm previously underexplored in Islamic finance. By incorporating this nuanced insight, our study provides a novel perspective on how Islamic banks can attain strategic equilibrium between risk management and performance improvement.